Comparison of two models for measuring radon exhalation rate with a ventilation chamber by numerical simulation. (1st October 2022) - Lin, F.; Xie, R.; Fan, Z.; Hu, T.; Mo, Y.; Liu, S.; Yuan, S.; Wang, L.; Yuan, H.; Tang, J.; Tan, Y.
Abstract: Two models can be used to measure the radon exhalation rate with a ventilation chamber. The first is the custom model with a flow meter, and the second is the improved model without flow meter. As the established radon exhalation standard facilities can't simulate any medium to be measured by adjusting the radon exhalation rate and effective decay constants as required, numerical simulation is useful to compare the two models for measuring radon exhalation rate under different effective decay constants. Three different effective decay constants and two different radon exhalation rates were simulated for measuring radon exhalation rates, and the simulation results confirmed that the improved model is quick and accurate even when the radon exhalation rate is very low. While the custom model can only be used to calculate the radon exhalation rates when the ventilation rate is far larger than the effective decay constant, and it takes a long time for the radon concentration inside the ventilation chamber to be stable. Therefore, the improved model without flow meter is more accurate to measure the radon exhalation rate under different effective decay constants.